2019
DOI: 10.1371/journal.pone.0212169
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences with a behaviour change intervention to enhance physical activity in primary care: A mixed methods study

Abstract: Objective To explore the experiences of patients at risk for cardiovascular disease in primary care with the Activate intervention in relation to their success in increasing their physical activity. Methods A convergent mixed methods study was conducted, parallel to a cluster-randomised controlled trial in primary care, using a questionnaire and semi-structured interviews. Questionnaires from 67 patients were analysed, and semi-structured interviews of 22 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The present data found that use of a wearable activity tracker can be enhanced if it is accompanied by a goal-setting message 31 provided in a timely manner (ie, teacheable moment), 32 when motivational messaging 32 would be most beneficial. The goal-setting message in the study focused on increasing the number of steps achieved at work by at least 10% of the baseline measurements.…”
Section: Discussionmentioning
confidence: 74%
“…The present data found that use of a wearable activity tracker can be enhanced if it is accompanied by a goal-setting message 31 provided in a timely manner (ie, teacheable moment), 32 when motivational messaging 32 would be most beneficial. The goal-setting message in the study focused on increasing the number of steps achieved at work by at least 10% of the baseline measurements.…”
Section: Discussionmentioning
confidence: 74%
“…Research has examined patients' willingness to receive behaviour change interventions within specific health contexts, such as during cancer screening appointments [19] or in the context of managing or preventing long-term health conditions including psoriasis [20] and cardiovascular disease [21], but have not considered consultations for conditions that may have little to do (at least from the perspective of the patient) with the target health behaviour. Consequently, more research is needed on the patient perspective of receiving opportunistic behaviour change interventions from GPs, during routine primary care consultations.…”
Section: Introductionmentioning
confidence: 99%
“…While demographic attributes have been correlated with health behaviors [6], they often do not fully explain differences in intervention effectiveness [7][8][9]. Similarly, comparisons within studies suggest that baseline participant traits such as age, sex, race/ethnicity and health status are not reliable predictors of participant response [10][11][12].…”
Section: Introductionmentioning
confidence: 99%